IMPLEMENTASI PENDIDIKAN BERBASIS KARAKTER DAN TEKNOLOGI DALAM MENGATASI TANTANGAN GLOBALISASI (STUDI KASUS DI SMA NEGERI 1 TANJUNG RAJA) - Neti Herawati; Suryanita Suryanita; Bahori Muslim (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The objective of this research is the implemenation of education based on character and technology which consist of planning, leading and oversighting coducting at SMAN 1 Tanjung Raja. This research designed to use qualitative approach, as well as case study method used as it’s methodelogy. Explanatory case study was used in this research with paticipant observation’ approach, a kind of case study where the data collected through paticipant observation, added with formal and informal interview as well as documents review. The conclusion of this research are (1) short, middle and long term plan conducted by stakeholders through meeting which is formed as shool’s vision and mission, (2) leading conducting through role model (3) oversighting cover both academic and managerial  activities conducted through “ SIMAK “ and counselling teacher.